Study of the 4p2, 5p2 and 5s5f excited configurations of the Zn and Cd isoelectronic sequences, using relativistic and non-relativistic semiempirical approaches - Di Rocco, Hector Omar (2016)
The consistency of the energy levels published for configurations 4p2, 5p2 and5s5f belonging to Zn and Cdisoelectronic sequences is studied. Different semiempirical approaches considering thelinearity of the Slater integrals for large Zc, the smoothness ofthe sF screeningparameters, the energy values in terms of Z (or Zc), and thedifferences of the Ecalc −Eexp values are used, whereEcalc values areenergies calculated with a Hartree-Hock method with relativistic corrections andsuperposition of configurations (HFR-SOC), and Eexp are the experimental values. Forthe np2 configurations bothLS andrelativistic jj expressions are considered. Configuration5s5f is also analyzed taking intoaccount the Landé’s interval rule.